Opto-electronic characterization of electron traps upon forming polymer oxide memory diodes - Chen, Q. (2013)
Metal-insulator-polymer diodes where the insulator is a thin oxide (Al2O3) layer are electroformed by applying a high bias. The initial stage is reversible and involves trapping of electrons near the oxide/polymer interface. The rate of charge trapping is limited by electron transport through the polymer. Detrapping of charge stored can be accomplished by illuminating with light under short-circuit conditions. The amount of stored charge is determined from the optically induced discharging current transient as a function of applied voltage and oxide thickness. When the charge density exceeds 8 1017/m2, an irreversible soft breakdown transition occurs to a non-volatile memory diode.